Myxopapillary ependymoma of cauda equina presented with communicating hydrocephalus and papilloedema : A case report - Ting, Siew Leng; Ahmad Tirmizi, Jobli; Sim, Sze Kiat; Dayangku Norlida, Awang Ojep (Malaysian Medical Association, 2019)
We reported a case of cauda equina myxopapillary ependymoma in a patient who presented with atypical history of progressive blurring of vision. Ophthalmology examination revealed relative afferent pupillary defect, binasal hemianopia and papilloedema. This case report serves as a reminder that the intraspinal tumour could be a cause of papilloedema, despite rare, should be considered in a hydrocephalus patient who presented with no intracranial pathology and minimal spinal symptoms.